interpersonal meaning in students' explanation texts - hadiani, dini (LPPM Universitas Mercu Buana Yogyakarta, 2019)
This study is aimed to investigate the interpersonal meaning in students’ explanation texts. Six texts taken from students’ writings were used as the instruments of text analysis. The theories of Systemic Functional Linguistics and explanation text were used as the framework of the text analysis. The findings show that students have employed mood types which are formed by the Subject and Finite as Mood element and predicator and complement as Residue. The arrangement of Subject and Finite in the clauses demonstrates that declarative mood is used dominantly in the texts to realize the speech function of a statement. It suggests that the students have attempted to provide the information to the readers which are relevant to the social function of the explanation text. Moreover, the little use of modality in students’ texts indicates that the students present factual information. This evidence has shown the students’ efforts to position themselves in the texts and to build relationships with the readers. In conclusion, students have been able to create an effective explanation text which is intended to inform how something is done.